'MN‐Clearwater', the first food‐grade intermediate wheatgrass (Kernza perennial grain) cultivar. Issue 3 (14th May 2020) - Bajgain, Prabin; Zhang, Xiaofei; Jungers, Jacob M.; DeHaan, Lee R.; Heim, Brett; Sheaffer, Craig C.; Wyse, Donald L.; Anderson, James A.
Abstract: 'MN‐Clearwater' (Reg. no. CV‐287, PI 692651) is the world's first commercial food‐grade intermediate wheatgrass [IWG; Thinopyrum intermedium (Host) Barkworth & D.R. Dewey subsp. intermedium ] grain cultivar. It was developed as a synthetic population at the University of Minnesota, St. Paul, MN, and released in August 2019. Intermediate wheatgrass is a perennial grain crop currently undergoing domestication and is known for its extensive long root system that can recycle soil nutrients and sequester carbon. MN‐Clearwater (experimental designation MN1504) was created by intercrossing seven parents selected for high grain yield, reduced shattering, high free grain threshing, reduced lodging, and uniform maturity. MN‐Clearwater was advanced for two generations before being evaluated in statewide yield trials, after which the fourth seed generation was released as the cultivar in a limited public release. In variety trials across Minnesota, MN‐Clearwater produced 696 kg ha −1 (621 lb ac −1 ) of grain with minimal lodging and negligible disease levels. The first 2 yr produce the highest grain yields under Minnesota conditions, and third‐year yields are significantly lower (average reduction of 77%) than the first 2 yr. As the first IWG cultivar released for sale under the Kernza trade name (The Land Institute), we expect this population to be a cornerstone resource for the IWG research community as well as for interested growers, food processors, and commercial partners. MN‐Clearwater grain is sold as Kernza perennial grain.